IMPROVING STUDENTS’ ENGLISH SPEAKING SKILL BY USING THEIR SPEAKING VIDEO RECORDING - Suadi Suadi (STAIN Sultan Abdurrahman Kepulauan Riau, 2020)
The background of the study was the phenomenon of the first semester students of class A English Language Education Department at STAIN Mandailing Natal. Most of them were seldom using English in everyday activity because they did not have enough motivation, adequate vocabulary, and self-confidence. To activate their speaking skill ability, it was used their speaking video recording. By this, they did not only speak, but also involved in correcting, commenting and evaluating their performance in speaking skill. It was productive solution to overcome their problem. The respondents of this study were 15 first semester students Class A English language Education department in STAIN Mandailing Natal. This study was categorized into Class Action Research (CAR). The method of data collection used in this study was form test of speaking video recording which was measuring seven aspects of speaking skill, they were (1) pronunciation, (2) fluency, (3) word choice, (4) structure, (5) self-confidence, (6) teamwork and (7) creativity. The result of cycle 1 showed that the students’ average score in speaking skill was 7.2. In the cycle 2, the students achieved far better average score namely 8.4. It means there was a progress on students’ speaking skill achievement after learning through speaking video recording. The conclusion was the use of speaking video recording was able to improve the students’ speaking ability because they were brave, motivated and interested to express English as the way they wanted it.